ANALYSIS OF CONTAMINATION OF ATMOSPHERE BY THE PUMP-CIRCULATION SYSTEM OF THE BORING SETTING - Шкіца, Л. Є.; Яцишин, Т. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
There has been analyzed the open part of the pumping-circulating system and movement of the drilling mud after its going out from the well. The sources were determined of the most intensive drilling mud evaporation at different parts of pumping-circulating system of the drilling rig changing due to the conduction of certain technological operations and production situations. The main factors that influence the state of the atmosphere in oil-and-gas mining sphere have been considered.